2017
DOI: 10.1097/01.ogx.0000512370.75143.9d
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Outcomes After Term and Preterm Delivery After Betamethasone Administration in Twin Pregnancies

Abstract: (Abstracted from Int J Gynaecol Obstet 2016;134:329–335) Prenatal betamethasone administration in singleton pregnancies is associated with a dose-dependent decrease in birth weight. This study aimed to determine the effects of betamethasone overall, and at different doses on fetal growth and neonatal outcomes in twin pregnancies based on fetal sex, chorionicity, and severity of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…And it has been suggested that there is a significant reduction in fetal growth velocity including head circumference, abdominal circumference, and estimated fetal weight in pregnancies exposed to ACS (Rizzo et al, 2022). As for twin pregnancies, ACS was found to reduce birth size of preterm neonates in a dose-dependent manner (Braun et al, 2016). Therefore, it is worth attention as impaired growth during pregnancy and infancy is in turn closely associated with neurodevelopmental disorders in the future.…”
Section: Short-term Risksmentioning
confidence: 99%
“…And it has been suggested that there is a significant reduction in fetal growth velocity including head circumference, abdominal circumference, and estimated fetal weight in pregnancies exposed to ACS (Rizzo et al, 2022). As for twin pregnancies, ACS was found to reduce birth size of preterm neonates in a dose-dependent manner (Braun et al, 2016). Therefore, it is worth attention as impaired growth during pregnancy and infancy is in turn closely associated with neurodevelopmental disorders in the future.…”
Section: Short-term Risksmentioning
confidence: 99%